Nafamostat mesylate versus regional citrate anticoagulation for chronic hemodialysis in patients at high risk of bleeding: a single-center, retrospective study - Jiangtao Li; Lirui Wang; Yuqiu Lu; Ying Zhou; Yue Chen (Renal Failure)
Introduction For hemodialysis patients at high risk of bleeding, a regional anticoagulant can be used, such as citrate or nafamostat mesylate (NM). The objective of this study was to evaluate NM as an alternative to citrate for anticoagulation in hemodialysis patients at high risk of bleeding.Methods This retrospective single-center study included consecutive patients in our dialysis center treated with either citrate or NM anticoagulation for hemodialysis from January 2022 to December 2023.The primary outcome was major clotting, defined as premature dialysis due to extracorporeal circuit clotting. The secondary outcome was the incidence of a major bleeding episode during or after hemodialysis.Results In total, 651hemodialysis sessions were performed in 196 patients and were compared (289 citrate and 362 NM anticoagulation). A lower number of premature dialysis due to clotting occurred in the NM sessions compared to citrate sessions (0.84% vs.5.19%, p = 0.001). NM was associated with a lower risk of major clotting compared with citrate during treatment (OR:0.063; CI: 0.008-0.475; p = 0.007). Regarding second outcome, no more major bleeding events related to NM occurred compared to citrate.Conclusion Among hemodialysis patients with high risk of bleeding, anticoagulation with NM, compared with citrate anticoagulation, provided relatively better efficacy, with no bleeding increment. NM is a valid alternative to citrate for hemodialysis patients at high risk of bleeding.